2020
DOI: 10.17159/2413-3051/2020/v31i4a8924
|View full text |Cite
|
Sign up to set email alerts
|

Beyond climatic intervention: The social dimension of a biogas project in Sogwala village, Zimbabwe

Abstract: There is now considerable interest to understand how local communities experiencing climatic risks can benefit from climate change responses. As this agenda unfolds, there is need to understand the impact of climate-related interventions from the perspective of local populations targeted by such projects. Existing assessment approaches tend to concentrate on the environmental and economic impacts of projects that minimise greenhouse gas emissions. This study assesses the social aspect of a domestic biogas proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…All were secondary analyses of the social impacts of climate interventions, which originally did not have a mental health focus (and hence did not meet our inclusion criteria and were not summarized narratively in our results). In one study based in Zimbabwe, it was found retrospectively that a biogas project contributed to community cohesion and empowerment 64 ; in another study based in China, planned relocation and sheltering was found to be protective against depression, anxiety, and PTSD symptoms among flood victims 65 . In contrast, a study conducted in six LMICs (Brazil, Cameroon, Indonesia, Peru, Tanzania, and Vietnam) concluded that the Reducing Emissions from Deforestation and Degradation (REDD+) initiative may have negatively impacted women’s wellbeing 66 .…”
Section: Discussionmentioning
confidence: 99%
“…All were secondary analyses of the social impacts of climate interventions, which originally did not have a mental health focus (and hence did not meet our inclusion criteria and were not summarized narratively in our results). In one study based in Zimbabwe, it was found retrospectively that a biogas project contributed to community cohesion and empowerment 64 ; in another study based in China, planned relocation and sheltering was found to be protective against depression, anxiety, and PTSD symptoms among flood victims 65 . In contrast, a study conducted in six LMICs (Brazil, Cameroon, Indonesia, Peru, Tanzania, and Vietnam) concluded that the Reducing Emissions from Deforestation and Degradation (REDD+) initiative may have negatively impacted women’s wellbeing 66 .…”
Section: Discussionmentioning
confidence: 99%
“…A village is a legal community unit with territorial boundaries to regulate and manage government affairs and local community interests based on community initiatives, origin rights, and traditional rights [2]. Those are recognized and respected in the government system of the unitary state of the Republic of Indonesia.…”
Section: Rural Developmentmentioning
confidence: 99%